Education and Movement of Boarding School Cleanliness Environmental Environment to Support Students' Health - Ruchiyat, Ruchiyat; Hairunnisa, Riva; Mariska, Ananta Tasya; Awaliah, Puput Fatimah; Fadila, Dila Nurul; Azahra, Salsa; Ananda, Citra; Kartika, Dita; Fauzi, Saddam Rexy; Lubis, Novriyanti (Fakultas Kewirausahaan Universitas Garut, 2025)
The health education program on skin diseases and environmental health conducted by the PKM Pharmacy Team of Garut University was held at the Tahfidz Qur’an Al-Yumna Islamic Boarding School in Garut, West Java. This program aimed to enhance the students' understanding and awareness of the importance of maintaining a clean and healthy lifestyle. The implementation methods included distributing brochures as an informational medium that could be re-read and delivering live presentations that allowed for two-way interaction. The results showed a significant improvement in students' understanding of various aspects, such as waste management using the 5R concept, ways to maintain environmental cleanliness, and the adverse effects of unclean environments. For example, understanding of waste sorting increased from 86% to 100% after the program. The program also emphasized the importance of personal hygiene to prevent contagious diseases like scabies, as well as maintaining water quality in accordance with health standards. Overall, the program successfully raised students' awareness and behavior regarding cleanliness and environmental health in the boarding school.